2015
DOI: 10.1038/ijo.2015.20
|View full text |Cite
|
Sign up to set email alerts
|

CD36 AA genotype is associated with decreased lipid taste perception in young obese, but not lean, children

Abstract: CD36 SNP A-allele, being present both in young lean and in obese children, is associated with high threshold for fatty acid taste sensitivity only in obese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 15 publications
7
68
1
2
Order By: Relevance
“…Homozygous individuals for the A allele showed a lower sensitivity to oleic acid than homozygous individuals for the G allele [9]. A similar finding was described by Mrizak et al [10] who observed that the AA genotype for this SNP was associated with a higher threshold of gustatory fat detection in Tunisian women and Algerian children [8]. A contrasting study held with a very small cohort ( n = 21) found that homozygous individuals for the G allele of the rs1761667 SNP had an 8-fold lower oleic acid detection threshold than AA individuals, although fat intake was not assessed [19].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Homozygous individuals for the A allele showed a lower sensitivity to oleic acid than homozygous individuals for the G allele [9]. A similar finding was described by Mrizak et al [10] who observed that the AA genotype for this SNP was associated with a higher threshold of gustatory fat detection in Tunisian women and Algerian children [8]. A contrasting study held with a very small cohort ( n = 21) found that homozygous individuals for the G allele of the rs1761667 SNP had an 8-fold lower oleic acid detection threshold than AA individuals, although fat intake was not assessed [19].…”
Section: Discussionsupporting
confidence: 67%
“…The CD36 AA genotype at rs1761667 has been associated with higher oral fat perception of salad dressings and self-reported acceptance of added fats and oils as well as obesity in African-American adults compared to carriers of the G allele [7]. On the other hand, other studies with North-African and Italian cohorts have reported that carriers of the A allele have a higher threshold detection for fatty foods and, as a result, a decreased taste perception of fat, but it was not investigated whether this modifies fat intake [8,9,10]. Additional research is required to better understand whether CD36 variants influence food intake.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has suggested that the detection of oral fat comprises a gustatory component [12]. There appears to be inter-individual variability with reported magnitudes of four-to forty-fold for the detection of free fatty acids among adults and children [4,13]. A number of mechanisms underlying oral fat detection have been purported, with the glycoprotein, CD36 appearing to play a key role as a prime fatty acid taste receptor, especially when concentrations are low [14].…”
Section: Discussionmentioning
confidence: 99%
“…O genótipo AA do rs1761667 foi associado à maior percepção de gordura em molhos para salada, ao relato de aceitação de gorduras e óleos adicionados, e à obesidade em adultos afrodescendentes em comparação com portadores do alelo G (60) . Por outro lado, outros estudos com coortes norte-africanas e italianas relataram que os portadores do alelo A têm um limiar de detecção maior para alimentos gordurosos, e como resultado, uma redução à percepção do sabor gorduroso, mas não foi investigado se ocorrem mudanças no consumo alimentar de gordura (64)(65)(66)(67) .…”
Section: Variações Nos Genes De Receptores De Sabor E Consumo Alimentarunclassified
“…Além disso, portadores do genótipo AA deste SNP apresentaram um limiar de detecção de gordura maior em mulheres da Tunísia (65) e um limiar mais elevado de sensibilidade ao sabor da gordura em crianças da Argélia (66) . Um resultado oposto realizado com uma pequena amostra (n=21) mostrou que os indivíduos homozigotos para o alelo G do rs1761667 tinham 8 vezes menor limiar de detecção de ácido oleico do que os indivíduos AA, embora não tenha sido observada associação com a ingestão de gordura (106) , semelhante ao encontrado por Keller et al que relatou que a presença do alelo A eleva o risco de consumo de gorduras (60) .…”
Section: Figura 7 Consumo De Achocolatado Em Pó Entre Obesos De Difeunclassified